Educational Supervision: Definition, Functions and Factors Influencing Educational Supervision - Asep Mulyana; Ahmad Fauzi; Egi Ginanjar; Farhatul Latifahi; Niken Listya Cahyani (Al-Ard: Journal of Education, 2025)
In the field of education and teaching, supervisors are needed who can dialogue and help personal and professional growth so that everyone experiences personal and professional improvement. The principal has the obligation to manage the running of the school and can also collaborate and relate closely with the community, raise the enthusiasm of the staff of teachers and school employees to work better, build and maintain family, cohesiveness and unity between teachers, staff and students. students, develop the school curriculum, know the school plan and know how to carry it out, pay attention to and strive for the welfare of teachers and staff. Supervision can be carried out by the school principal who acts as a supervisor, although in the modern educational organization system a special supervisor is needed who is more independent, and can increase objectivity in coaching and carrying out his duties. The function of monitoring or supervision in education is not just control to see whether all activities have been carried out in accordance with the plans and programs that have been outlined, but more than that. Supervision in education has a broader meaning. Supervision activities include determining the conditions or requirements for personnel and materials needed to create an effective teaching and learning situation, and efforts to fulfill these requirements.